confined. designed. but credited? - Kraemer, Anna (My University, 2021)
confined. designed. but credited? was created to illustrate the history, or lack thereof, of women in the graphic design profession. This zine explores the contributions of 10 key women to the field of graphic design. Analyzing and comparing the texts The Second Sex by Simone de Beauvoir, and Alms for Oblivion by Ellen Mazur Thomson brings attention to the disparities and struggles of career women. Beauvoir’s comment on existentialism focuses on navigating individualistic thinking with the tension between free will and societal constraints. Despite oppression and sexism, multiple women achieved professional status as graphic designers. However, women were forced into more “feminine” specialties at design schools such as the Bauhaus and/or were “lost” to history because, according to Thomson, they were not credited for their work. In addition, exploring the primary and secondary sources questions the definition of design itself and why the lack of clarity has made it difficult to identify women designers. Delivering this research in the form of a zine salutes one of the ways feminists communicate their views. The combination of photos, hand-drawn illustrations, and digitally rendered shapes & textures help point to the main ideas of each article. Overall, the zine captures key concepts of limitations within a male-dominated world, as well as the capacity, competence, and innovation of women in design. Created for the Feminist Theories and Foundations course (GEND219) and informed by my program, Bachelor of Design.
Keywords: women; graphic design; history; gender disparity